The Macroalgae Ecological Quality Index (MEQI) in the Basin of Mexico: a proposal of aquatic bioindicators for peri-urban rivers - Javier Carmona-Jiménez; Victor Hugo Salinas-Camarillo; Angela Caro-Borrero (Revista Mexicana de Biodiversidad)
We assessed macroalgal responses to anthropogenic pressures in the Basin of Mexico to examine whether these biological indicators exhibited a discriminatory and explanatory correlation for the ecological quality evaluation reflected in the Macroalgae Ecological Quality Index (MEQI). The proposal included three steps: i) characterization of trophic level and hydromorphological quality (HQ) in 49 sites collected between 2012 and 2016 with different conservation degrees; ii) calculation of the indicator value of 20 taxa and the algorithm proposal; and iii) validation of the algorithm in 26 new sites and its correlation with water quality and HQ. The ecological quality gradient to which the macroalgae responded was related to oxygen saturation, soluble reactive phosphorus, dissolved inorganic nitrogen, and hydromorphological quality. By assigning an indicator value to each group of species, we calculated the MEQI using the formula adapted from Pantle and Buck, indicating five different ecological quality classes. The MEQI index allowed to established good quality reference sites and also established altered sites in chemical composition and structure. Therefore, MEQI are recommended for biomonitoring in the Basin of Mexico and the registration of its multiple stressors.